Innervation of the thoracolumbar fascia - Mense, Siegfried (European journal of translational myology, 2019)
The aim of the study was to obtain information on the sensory functions of the thoracolumbar fascia (TLF). The types of nerve fibres present in the TLF were visualized with specific antibodies to neuropeptides and sympathetic fibres. Most data were obtained from the TLF in rats, but some findings from the human fascia are also included. The only receptive nerve ending found was the free nerve ending, i.e. no corpuscular receptors existed in our specimen. An exclusive innervation with free nerve endings speaks for a nociceptive function, but the TLF may also fulfill proprioceptive functions, since many of the free nerve endings have a low mechanical threshold. Most of the fibres could be visualized with antibodies to CGRP [calcitonin gene- related peptide (CGRP)] and SP [substance P (SP)]. The latter ones most likely were nociceptors. The TLF contained a great proportion of postganglionic sympathetic fibres, which may be vasoconstrictors. A comparison between an inflamed and intact fascia showed an increase of the CGRP- and SP-positive fibres in the inflamed TLF. This finding could be one explanation for the low back pain of many patients, since practically all lesions of the fascia are accompanied by a sterile inflammation.
Gesehen am 23.10.2020